Histological Study of Tumour Budding in Colorectal Adenocarcinoma and its Association with Tumor Stage and Nodal Status - Rampada, Sasmal Prasanjit; Philipose, Thoppil Reba (Annals of Pathology and Laboratory Medicine, 2022)
Introduction: CRC is commonest human carcinoma and leading causes of cancer-related death worldwide. â€œTumor buddingâ€ is 4 or more tumor cells in invasive front of colorectal adenocarcinoma glands invading up to adjacent stroma, can act as independent prognostic marker for tumor staging which changes prognosis and further treatment plans Objective: Association of tumor budding with stage of tumour and lymph node status. Methods: This is a retrospective study from Jan 2019 â€“ Jan 2022. H&E sections prepared from resected total/hemi/partial colectomy specimens to assess tumor bud count following International tumour budding consensus conference (ITBCC) 2016 criteria â€œTumour budding assessed in 1 hotspot (in a field measuring 0.785 mm2) at the invasive front with average 10 consecutive fields with highest bud count in one field (hotspot) under 200x magnifications (field area=0.785 mm2) using Magnus Decahead microscope. The budding was graded as low (0-4 buds), intermediate (5-9 buds), high (10 or more buds). Results: Analysis done according to ITBCC tumor bud scoring shows increased tumor budding is associated with positive higher tumor grade (p value: 0.026) and stage (p value - 0.024) but not with nodal status (p value: 0.096). Conclusion: Current study shows tumor bud score is associated with positive lymph node status, higher tumor grade and stage. However, the study needs to be validated by a larger sample size and follow up studies.